Energy Adequacy Rate and Desirable Dietary Pattern of Horticultural Farmer Household in Probolinggo Regency during COVID-19 Pandemic - Asterina, Rika; Nuhfil Hanani; Fahriyah (HABITAT, 2022)
Household food security is an important concern for the government because it can describe food security in the smallest unit, namely household consumption. One of the government's policies regarding food security on the side of food absorption is through the Law of the Republic of Indonesia Number 18 of 2012 namely the fulfillment of diverse, nutritious, balanced, and safe food consumption patterns. The research objectives are (1) To analyze the food security of horticultural farmers' households in terms of the Energy Adequacy Rate (EAR) in Probolinggo Regency, (2) To analyze the food security of horticultural farmers' households as seen from the Desirable Dietary Pattern (DDP) in Probolinggo Regency, and (3) To analyze the factors that influence the Desirable Dietary Pattern (DDP) in Probolinggo Regency. The results showed that food security in terms of quantity and quality still did not meet the recommendations. The actual EAR of horticultural farmers in Probolinggo Regency is 1867.76 kcal/capita/day, which is still below the normative or recommended EAR of 2,100 kcal/capita/day. The actual DDP score is 74.15 which states that the actual DDP is still below the normative DDP of 100. Two parameters have a significant effect on the dependent variable, namely farm income (X1) and dummy nutrition knowledge of housewives (DX2), while dummy education head of household (X3) has no significant effect.